(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Nowadays, free trade mechanism will be continously implemented. Regarding those conditions, the increasing export of manufacture rubber comodities can be reach, only if they have a comparative and a competitive advantage than other exporting countries. These efforts must begin with the improvement quality of rubber raw materials at farm level by removing five main inhibiting factors such as: (1) farmers group doesn’t play a role as a bussiness unit (2) the demand of quality materials of crumb rubber industry is very low; (3) the dominant of trades in the marketing of raw rubber materials; (4) there is no advantageous partnership pattern, and, (5) the mechanism of attractive differential price for better quality not available for unsmoked sheet and slice slap. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Dalam era perdagangan bebas yang akan terus bergulir, peningkatan ekspor produk karet olahan hanya dapat ditempuh bila memiliki keunggulan komparatif dan kompetitif dari negara pesaing. Upaya kearah itu harus dimulai dari perbaikan kualitas bokar di tingkat petani, dengan menghilangkan lima faktor penghambat utama yaitu: (1) belum berperannya kelompok tani sebagai unit bisnis, (2) permintaan bahan baku inustri karet remah yang masih berorientasi kepada bokar berkualitas rendah, (3) dominasi pedagang dalam pemasaran bokar, dan (4) belum adanya pola kemitraan yang saling menguntungkan, (5) belum terlaksananya penentuan harga sesuai kualitas yang menarik bagi produk sheet angin dan slab giling.